UNRAVELING THE MULTIFACETED TAPESTRY: A COMPREHENSIVE EXAMINATION OF DYNAMICS AND CHALLENGES IN ENTREPRENEURSHIPDEVELOPMENT WITHIN INDONESIA - Silvia Ekasari (CV. Adiba Aisha Amira, 2025)
Entrepreneurship development in Indonesia is a complex and multifaceted phenomenon influenced by various factors. This study comprehensively examines the dynamics and challenges shaping entrepreneurship within the Indonesian context. It explores the role of government policies, education and training initiatives, access to finance, supportive infrastructure, international collaborations, and cultural, economic, and regulatory factors in fostering or hindering entrepreneurship. Through a thorough literature review, this study provides insights into the intricacies of entrepreneurship development in Indonesia, highlighting key findings and implications for policymakers, practitioners, and researchers. By unraveling the multifaceted tapestry of entrepreneurship in Indonesia, this study aims to contribute to a deeper understanding of the entrepreneurial landscape and inform strategies for promoting sustainable entrepreneurship development in the Country.